Mud Houses in Nepal: Balancing Tradition, Sustainability and Modern Needs - Dhanchha, Shrutina (Scientific Researches in Academia, 2024)
Mud houses are a resilient alternative housing option, offering natural cooling, cost-effectiveness, longevity, and earthquake resilient. The increasing prevalence of concrete buildings spurred by urbanization and disasters exacerbates environmental concerns, fueling the resurgence of sustainable technologies such as traditional mud construction. This article employs a systematic literature review methodology to conduct a comprehensive search of scholarly articles, books, reports, and other relevant sources related to mud houses in Nepal and around the world. This paper delves into the challenges and opportunities associated with balancing tradition, sustainability, and modern needs concerning mud buildings in Nepal, emphasizing the importance of cultural perspectives and theoretical frameworks in preserving Nepal's architectural heritage. The findings emphasize community involvement in mud house construction, with traditional skills passed down through generations, extending to knowledge transfer initiatives, advocating for educational programs and workshops empowering communities to sustain traditional construction methods while embracing modern advancements when appropriate.